Effect of mentorship on regular teachers’ self-efficacy towards implementation of inclusive education at basic education level - Adaka, Terfa; Adigun, Olufemi; Lalu, James; Mngomezulu, Thanduxolo (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Impaired teachers’ self-efficacy has contributed to delays in the implementation of inclusive education in Nigeria. Unfortunately, several efforts established towards ensuring the actualization of the Salamanca Declaration in Nigeria are yet to produce desired results. Although some past studies identified a mentor-mentee approach as a model that promotes the efficient implementation of established policies, paucity of research evidence exists on the implication of mentor-mentee approaches on the construction of teachers’ self-efficacy for inclusive education, particularly at the basic level of education. Objectives. This study was conducted to investigate the effect of mentorship on in-service regular teachers’ self-efficacy towards the implementation of inclusive education at the basic education level in Gombe State, Nigeria. Methods. A quasi-experimental research design was adopted for the study, while a purposive sampling technique was used to select 42 participants aged between 20 and 45 (M = 33.90, SD = 6.35) from two local government areas of the Gombe South Senatorial District. Participants were assigned to treatment and control groups, with 21 participants in each group. The Teachers’ Sense of Efficacy Scale (α = .81) was used for data collection. Data collected was analysed with an independent sample t-test. Results. Findings showed the efficacy of a mentoring training program on the self-efficacy of in-service regular teachers towards effective implementation of inclusive education at the basic level of education. Also, male and older teachers had higher self-efficacy for the implementation of Inclusive education at the basic education level. Conclusion. Mentorship programs significantly facilitate the achievement of inclusive education, particularly at the basic level of education. Well-designed mentorship programs for early career in-service regular teachers would equip them with an orientation that would guide them towards effective implementation of inclusive education at the basic level of education. Based on the outcome of the study appropriate mentorship strategy for novice teachers was recommended.
Keywords: inclusive education; mentorship; teacher self-efficacy; basic education